Dynamics of intracellular clathrin/AP1- and clathrin/AP3-containing carriers - Kural, Comert; Boulant, Steeve (Cell reports, 2012)
Summary Clathrin/AP1- and clathrin/AP3-coated vesicular carriers originate from endosomes and the trans-Golgi network. Here, we report the real-time visualization of these structures in living cells reliably tracked by rapid, three-dimensional imaging with the use of a spinning-disk confocal microscope. We imaged relatively sparse, diffraction-limited, fluorescent objects containing chimeric fluorescent protein (clathrin light chain, σ adaptor subunits, or dynamin2) with a spatial precision of up to ∼30 nm and a temporal resolution of ∼1 s. The dynamic characteristics of the intracellular clathrin/AP1 and clathrin/AP3 carriers are similar to those of endocytic clathrin/AP2 pits and vesicles; the clathrin/AP1 coats are, on average, slightly shorter-lived than their AP2 and AP3 counterparts. We confirmed that although dynamin2 is recruited as a burst to clathrin/AP2 pits immediately before their budding from the plasma membrane, we found no evidence supporting a similar association of dynamin2 with clathrin/AP1 or clathrin/AP3 carriers at any stage during their lifetime. We found no effects of chemical inhibitors of dynamin function or the K44A dominant-negative mutant of dynamin on AP1 and AP3 dynamics. This observation suggests that an alternative budding mechanism, yet to be discovered, is responsible for the scission step of clathrin/AP1 and clathrin/AP3 carriers.